Unlocking Investment Potential: The Impact of Financial Knowledge on University Students' Investment Intentions Through Financial Attitude - Utami, Eristy Minda; Nursjanti, Farida; Amaliawiati, Lia; Komariah, Siti (Husnayain Business Review, 2025)
Purpose – This study analyzes the influence of financial knowledge on students' investment intentions, with financial attitude as a mediating variable. In the context of the increasing importance of financial literacy among Generation Z, this research explores how financial education shapes the investment behavior of students enrolled in capital market courses at Widyatama University. Methodology/Approach – This study employs a survey of 200 undergraduate students taking capital market courses. The analysis is conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach to examine the relationships between financial knowledge, financial attitude, and investment intention. A 5-point Likert scale is used to measure the studied variables. Findings – The results indicate that financial knowledge significantly influences students' financial attitudes, which in turn positively impact their investment intentions. Mediation analysis confirms that financial attitude plays a key role in linking financial knowledge to investment intention. While financial knowledge directly affects investment decisions, students with a stronger financial attitude are more motivated to invest. Novelty/Value – This study provides deeper insights into the investment behavior of university students in Indonesia by highlighting the mediating role of financial attitude. The findings suggest that financial literacy programs should not only focus on increasing knowledge but also on fostering a positive financial attitude to encourage active participation in the capital market.